Monitoring Bakteri Coliform pada Pasir Pantai dan Air Laut di Wisata Pantai Marina dan Pantai Baruna - Wilis Ari Setyati; Delianis Pringgenies; Dony Bayu Putra Pamungkas; Chrisna Adhi Suryono (Jurnal Kelautan Tropis, 2022)
Marina and Baruna Beach are widely recognized as popular beach tourism destinations in Semarang. Its proximity to the main beach estuary causes them to significantly impact marine tourism quality. In addition, their exposure to waste may be a potential threat to biological pollution. Coliform and Escherichia coli are used as bioindicators to monitor the quality of marine tourism due to their high correlation to faecal contamination and pathogenic microbes. Samples collected were beach sand and seawater from Marina Beach, Baruna Beach and the estuary of Semarang Banjir Kanal Barat. Data were collected following the presumptive and confirmed test, followed by the conversion to MPN Table. Data obtained is combined with Government Regulations No. 22 of 2021 in Appendix VIII, specifically seawater quality standards for marine tourism. The results of this study reveal high contamination of coliform and E. coli in both beaches. Coliform result in the swimming zone at Marina Beach was 2800 MPN/100ml and at Baruna Beach was 16000 MPN/100ml. Meanwhile, Escherichia coli in the swimming zone area at Marina Beach was 400 MPN/100ml and at Baruna Beach was 1700 MPN/100ml. Overall, these results show that the contamination rate from both swimming zones is higher than the recommended seawater quality standard for marine tourism  Wisata Pantai Marina dan Pantai Baruna menjadi kawasan wisata pantai yang populer di Kota Semarang. Lokasinya yang berdekatan dengan muara sungai utama di Kota ini berdampak terhadap kualitas wisata pantai. Paparan limbah berpotensi menyebabkanpencemaran biologis. Monitoring terhadap bakteri coliform dan bakteri Escherichia coli dapat digunakan sebagai bioindikator kualitas wisata pantai, karena keberadaannya berkorelasi dengan cemaran feses dan mikroba patogen. Sampel berupa pasir pantai dan air laut diambil dari  lokasi Pantai Marina, Pantai Baruna, dan muara Sungai Banjir Kanal Barat Kota Semarang. Pengujian sampel dilaksanakan dengan presumtif test dan confirmed test, selanjutnya dikonversi dengan Tabel MPN. Data yang didapatkan akan dipadukan dengan PP Nomor 22 Tahun 2021 pada Lampiran VIII, yaitu baku mutu air laut untuk wisata bahari. Hasil penelitian menunjukkan tingginya kontaminasi bakteri coliform dan bakteri Escherichia coli dikedua pantai. Hasil coliform pada kawasan swimming zone pada Pantai Marina 2800 MPN/100ml dan Pantai Baruna 16000 MPN/100ml, serta hasil Escherichia coli pada kawasan swimming zone pada Pantai Marina 400 MPN/100ml dan Pantai Baruna 1700 MPN/100ml. Kawasan swimming zone pada wisata Pantai Marina dan Pantai Baruna mempunyai hasil yang melebihi baku mutu air laut untuk wisata bahari.